SEROLOGICAL MARKERS OF VIRAL, SYPHILITIC AND TOXOPLASMIC INFECTION IN CHILDREN AND TEENAGERS WITH NEPHROTIC SYNDROME: CASE SERIES FROM MATO GROSSO STATE, BRAZIL - Soares, Silvania França da Silva; Donatti, Teresinha Lermen; Souto, Francisco José Dutra (Revista do Instituto de Medicina Tropical de São Paulo, 2014)
Some infections can be the cause of secondary nephrotic syndrome. The aim of this study was to describe the experience of a Renal Disease Reference Clinic from Central Brazil, in which serological markers of some infectious agents are systematically screened in children with nephrotic syndrome. Data were obtained from the assessment of medical files of all children under fifteen years of age, who matched nephrotic syndrome criteria. Subjects were tested for IgG and IgM antibodies against T. gondii and cytomegalovirus; antibodies against Herpes simplex, hepatitis C virus and HIV; and surface antigen (HBsAg) of hepatitis B virus. The VDRL test was also performed. 169 cases were studied. The median age on the first visit was 44 months and 103 (60.9%) patients were male. Anti-CMV IgG and IgM were found in 70.4% and 4.1%, respectively. IgG and IgM against Toxoplasma gondii were present in 32.5% and 5.3%, respectively. Two patients were positive for HBsAg, but none showed markers for HIV, hepatitis C, or Treponema pallidum. IgG and IgM against herpes simplex virus were performed on 54 patients, of which 48.1% and 22.2% were positive. IgM antibodies in some children with clinical signs of recent infection suggest that these diseases may play a role in the genesis of nephrotic syndrome.